A social realist analysis of the professional identity formation of lecturers emerging from completing professional development at a South African research-intensive university - Adams, Anthea (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning)
This doctoral study is part of a Department of Higher Education and Training (DHET) capacity development project, Phakamisa. Using Margaret Archer's Social Realism as a substantive theory and methodological tool and Roy Bhaskar's Critical Realism as a meta-theory, I was able to identify and explain the interplay between the structural, cultural and agential mechanisms within a professional development course that enabled or constrained the emergence of lecturers' professional academic identities. My research participants are fourteen lecturers who completed the Postgraduate Diploma in Higher Education (PGDip HE) at Rhodes University between 2007 and 2017. Social Realism's explanatory methodologies, analytical dualism, and the morphogenetic cycle allowed me to provide causal explanations and account for the historicity of the emergence of lecturers' professional academic identities as teachers. A qualitative research design involving case study research allowed me to search for generative mechanisms to understand and explain the conditioning influence of often unobservable phenomena and underlying mechanisms in developing lecturers' identities as teachers in a research-intensive university. As strong social actors imbued with power and material resources, university leadership should consider the constraining influence of contextual conditions, such as the hegemony of disciplinary research versus research in the Scholarship of Teaching and Learning (SoTL). The socio-cultural (S-C) interactions of the fourteen lecturers (agents) signal the possibilities for structural, cultural and agential morphogenesis when agents choose to exercise their agency, i.e., their personal emergent properties (PEPs) to mediate prevalent structural and cultural emergent properties (SEPs and CEPs) enabling or constraining their personal projects. Lecturers' personal projects are the courses of action they intentionally engage in as they strive to establish sustainable yet evolving practices as teachers in their disciplines. This thesis shows that exercising their PEPs involves subjective reflexivity and transforming from primary agents to corporate agents due to collective action and alliances with like-minded peers and colleagues to shape the teaching and learning agenda in their respective departments and the broader higher education context. Triple morphogenesis of lecturers' agency occurred through their realisation as social actors. It signified the formation of their professional identities as teachers and how they uniquely embodied and enacted their teacher roles.,Hierdie doktorale studie is deel van 'n Departement van Hoër Onderwys en Opleiding (DHOO) kapasiteitsontwikkelingsprojek, naamlik Phakamisa. Deur gebruik te maak van Margaret Archer se Sosiale Realisme ("Social Realism") as 'n substantiewe teorie en metodologiese instrument, en Roy Bhaskar se Kritiese Realisme ("Critical Realism") as 'n metateorie, was ek in staat om die wisselwerking tussen die strukturele, kulturele en agentiese meganismes binne 'n professionele ontwikkelingskursus te identifiseer en te verduidelik wat die ontstaan van dosente se professionele akademiese identiteite moontlik gemaak of beperk het. Die deelnemers in my navorsing is veertien dosente wat die Nagraadse Diploma in Hoër Onderwys (NGDip HO) aan Rhodes Universiteit tussen 2007 en 2017 voltooi het. Sosiale Realisme se verklarende metodologieë, analitiese dualisme en die morfogenetiese siklus het my toegelaat om oorsaaklike verklarings te verskaf en die historisiteit van die ontstaan van dosente se professionele akademiese identiteite as onderwysers te verantwoord. 'n Kwalitatiewe navorsingsontwerp wat gevallestudienavorsing behels het, het my toegelaat om na generatiewe meganismes te soek om die kondisionerende invloed van dikwels onwaarneembare verskynsels en onderliggende meganismes in die ontwikkeling van dosente se identiteit as onderwysers in 'n navorsingsintensiewe universiteit te verstaan en te verduidelik. As sterk sosiale rolspelers deurdrenk met mag en materiële hulpbronne, behoort universiteitsleierskap die beperkende invloed van kontekstuele toestande, soos die hegemonie van dissiplinÃªre navorsing versus navorsing in die Akademieskap van Onderrig en Leer (AvOL, of in Engels "Scholarship of Teaching and Learning", afgekort na SoTL) in ag te neem. Die sosiokulturele (S-K) interaksie van die veertien dosente (agente) dui op die moontlikhede vir strukturele, kulturele en agentiale morfogenese wanneer agente doelbewus kies om hul agentskap uit te oefen, dit wil sÃª hul persoonlike ontluikende eienskappe (in Engels "personal emergent properties", afgekort na PEPs) om heersende strukturele en kulturele ontluikende eienskappe te bemiddel (in Engels "cultural emergent properties", afgekort na CEPs) wat hul persoonlike projekte moontlik maak of beperk. Dosente se persoonlike projekte is die aksies wat hulle doelbewus aangepak het terwyl hulle daarna gestreef het om volhoubare dog ontwikkelende praktyke as onderwysers in hul dissiplines te vestig. Hierdie tesis dui aan dat die uitoefening van hul persoonlike ontluikende eienskappe ("PEPs") behels subjektiewe refleksiwiteit en transformasie van primÃªre agente na korporatiewe agente as gevolg van kollektiewe optrede en alliansies met eendersdenkende eweknieë en kollegas om die onderrigen leeragenda in hul onderskeie departemente en die breër hoëronderwyskonteks te beÃ¯nvloed. Drievoudige morfogenese van dosente se agentskap het plaasgevind deur hul verwesenliking as sosiale rolspelers. Dit het die vorming van hul professionele identiteite as onderwysers aangedui en die unieke manier hoe hulle hul onderwyserrolle interpreteer en uitleef.
Keywords: Identity (Psychology) in education; Academic development; Staff development; Social realism; Critical realism; Scholarship of teaching and learning; Education, Higher -- South Africa